Nanowhisker glues for fatigue-resistant bioadhesion and interfacial functionalization - Shuaibing Jiang; Tony Jin; Tianqin Ning; Zhen Yang; Zhenwei Ma; Ran Huo; Yixun Cheng; Davis Kurdyla; Edmond Lam; Rong Long; Audrey Moores; Jianyu Li (Nature Communications)
Abstract Fatigue-resistant functional bioadhesion is desired in diverse applications ranging from wound management to wearable devices. Nanoparticle-based bioadhesives offer versatile functionality but suffer from weak adhesion and fatigue vulnerability due to tissue barriers and poor tissue interactions. Polymer chain-based bioadhesives can form tough bioadhesion but remain vulnerable to fatigue fracture. Here we demonstrate that rationally designed chitosan nanowhiskers glues achieve fatigue-resistant bioadhesion and interfacial functionalization via the combined high aspect ratio, rigidity, polymer-binding and network-forming properties. We deploy these glues using chemical enhancers, microneedle rollers, and ultrasound, enabling strong tissue anchorage despite tissue barriers. At low concentrations, the nanowhisker glue paired with a tough hydrogel achieves an interfacial fatigue threshold of 382 J m−2 and adhesion energy exceeding 1000 J m−2. Transmission electron microscopy reveals a sandwiched nanowhisker layer interpenetrated with both hydrogels and tissues, creating an interface of high stiffness and strength that kinks and arrests interfacial cracks, ensuring unprecedented fatigue resistance. Further, the nanowhisker glue allows for versatile functionalization at the interface such as photothermal and sonodynamic effects. This work expands the performance and functionality of bioadhesives, opening new possibilities for medical and engineering applications.